What influence do face masks have on reading emotions in faces? - R. Kleiser; T. Raffelsberger; J. Trenkler; S. Meckel; R.J. Seitz (Neuroimage: Reports, 2022)
In the past years, no event has affected people around the globe more than the SARS-COVID-2 pandemic. Besides the health system and the economy, it has affected social life. A grave sequela is the social distancing due to the ubiquitous use of medical face masks. Since these face masks cover approximately two thirds of the face including the mouth and nose, we hypothesized that they may impair affect reading of emotional face expressions. We used functional magnetic resonance imaging in 16 healthy volunteers to investigate brain activity changes related to the recognition of evolving emotional face expressions in short video-clips. We found that the face masks delayed emotion recognition, but at a normal nearly 100% success rate. This effect was related to a decreased activation in the cortical network mediating face recognition. Our data support the notion that face masks can have an adverse impact of social interactions.